PENGARUH MEDIA INTERAKTIF POWERPOINT MATERI KEBERAGAMAN SUKU BANGSA DAN BUDAYA DI INDONESIA UNTUK MENGEMBANGKAN HASIL BELAJAR SISWA KELAS IV (EMPAT) SD - Icha Tantri Lestari; Imamudin; Munawaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Quantitative research is a method used to answer research problems related to data in the form of numbers and statistical programs. This study aims to determine the effect of using interactive PowerPoint media to develop the learning outcomes of fourth-grade elementary school students on the material of ethnic and cultural diversity in Indonesia. This study uses data collection techniques including pretest and posttest tests, questionnaires, documentation. The type of research "Quantitative Experiment" with a quasi-experimental method, the research design uses Posttest-Only Control Design, the sample technique is purposive sampling, the number of which is 50 where the experimental class consists of 25 students and the control class 25 students. The results of the study showed an increase in the average pretest score of the experimental class by 59.20 to 77.68 in the posttest while the average pretest score of the control class was 58.00 to 75.80 in the posttest. The independent sample t-test produced a significant value of 0.001 <0.05, which means there is a significant difference before and after treatment. Thus, it can be concluded that interactive PowerPoint media has an effect on developing the learning outcomes of elementary school students.